Hladno Pivo: Shamar, Croatia
Band: Hladno Pivo (Cold Beer), Title: Šamar. The CD-ROM was made in the framework of “Musko NE Nasilju nad Zenama (Men's NO to Violence against Women), 16 Days Campaign, Croatia ” in 2002 with the financial support of the Republic France and B.a.B.e. (Budi aktivna, Budi emancipirana - Be active, Be emancipated)